PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN KINERJA CV. RANDU SARI SATU TAHUN 2016-2018 - Novi Riani (Universitas Muhammadiyah Metro Lampung, 2020)
In evaluating what has been achieved by CV. Randu Sari Satu then for an estimate of the changes in the financial condition of the business CV. Randu Sari Satu requires financial calculations with ratio analysis. Based on the background of the research above, the problem raised in this study is whether the financial ratios in 2016-2018 affect changes in performance on the CV. Randu Sari Satu? Based on the above problem formulation, the purpose of this study is to determine the effect of financial ratios on changes in performance on the CV. Randu Sari Satu. This research is focused on problem solving aimed at explaining the relationship between one variable with another variable in a qualitative and quantitative analysis. Based on the results of research and discussion, conclusions can be drawn namely current ratio, quick ratio, working capital to total assets, total debt to equity ratio, total debt to total capital assets, long term debt to equity ratio, total asset turnover, inventory turnover, average days inventory, working capital turnover, gross profit margin, net profit margin, return on investment and return on equity have no effect on changes in company performance. Based on the conclusions above, the following suggestions can be given To CV. Randu Sari Satu to further review the performance of CV. Randu Sari Satu which is run, it is intended to increase the benefits gained by CV. Randu Sari Satu. So the performance of CV. Randu Sari Satu can run according to the goals set. In this study, researchers measured the effect of financial ratios on changes in CV performance. Randu Sari One year 2016-2018. This research was carried out in a limited manner with the determination of population and sample in CV. Randu Sari Satu. The next researcher is expected to be able to develop other aspects and be able to use this research as a source of research material in subsequent studies. Keywords:Financial Ratios, Performance, CV. Randu Sari Satu